If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 2x + 6 Reorder the terms: 2(-2 + x) = 2x + 6 (-2 * 2 + x * 2) = 2x + 6 (-4 + 2x) = 2x + 6 Reorder the terms: -4 + 2x = 6 + 2x Add '-2x' to each side of the equation. -4 + 2x + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 0 = 6 + 2x + -2x -4 = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 = 6 + 0 -4 = 6 Solving -4 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9x+5=4(2x-1)+9 | | 4(5x+3)+5=13x+3 | | -13+4x=-52+25 | | 3ax+12ax-36a=0 | | 4+91x=39x+12 | | (x+2)(x+5)=18 | | (3v-6)/3v | | .5(x+30)+1.1x=79 | | -(-2a-3)-5=-3(a-6) | | c^2d^2-4cd+4=0 | | -4(x+1)=-1(x+5) | | a^6-7a+a-7=0 | | 3(25-b)+b=35 | | x^3-7x^2+6=0 | | -2-(-8)-7+3= | | 9x^2-20x+2=0 | | -4k-(3-7k)=15 | | 4b-6b+7=9 | | 7=5c+22-10c | | 2w-7w+3=-22 | | 46=4x-4+6x | | -7w-(w+4)=12 | | 5(x-2)+3=-3(2x+1)-6 | | 7m+20-10=-25 | | 36r^2-60r+25=0 | | 15y-(-5y+36)=24 | | 12+x+9=37 | | x^2-6x-y^2+7=0 | | -98y^2-26=0 | | x+15+19=41 | | 40x+35y=720 | | 9aq^4-9an^4=0 |